Small state referendums : lessons from New Zealand - Morris, Caroline, 1973- (Abingdon, Oxon [UK] ; New York, NY : Routledge, 2024)
"This book explores the unusual and unique experience of direct democracy in the small state of New Zealand, where referendums have been a persistent feature of the political landscape for over a century. Referendums have been the site of renewed interest from scholars, seeking to respond to what they term the 'democratic deficit' in otherwise stable and functional Western democracies. They have also been at the heart of many divisive and important political and social moments in recent history, from the UK's Brexit referendum in 2016 to the disputed legitimacy of the 2022 referendums in Russian-occupied Ukraine. This book fills an important gap in the literature through an extended study of the law and practice of referendums in the small Commonwealth state of New Zealand. It also expands the field of small state democracy studies by applying the insights of this field to the direct democracy experience of a small state. With the inclusion of comprehensive tables of referendums and legislative materials, this book will be of interest to scholars of direct democracy and small states, politicians, legislators and policy makers and all those with a desire to do democracy better"--
Introducing referendums and the small state -- The New Zealand experience of the referendum -- Three Referendums in context.
Keywords: People (Constitutional law) -- New Zealand; Referendum -- New Zealand; Representative government and representation -- New Zealand; Election law -- New Zealand; Proportional representation -- New Zealand; Political participation -- New Zealand; Referendum; New Zealand -- Politics and government; LAW / Constitutional; POLITICAL SCIENCE / Political Ideologies / Democracy; LAW / Comparative